Analisis Keragaman Genetik Isolat Bakteri Xanthomonas oryzae pv. oryzae dari Jawa Barat dan Jawa Tengah Berdasarkan Analisis ARDRA Gen 16SrRNA - Yadi Suryadi; Dwi N. Susilowati; Puji Lestari; Sutoro Sutoro; Ifa Manzila; Trini Suryani Kadir; Sheryn Sunni Albani; I Made Artika (Jurnal Fitopatologi Indonesia, 2014)
Fifteen Xanthomonas oryzae pv. oryzae isolates from several regions in West Java and Central Java have been studied for their genetic diversity using amplified ribosomal DNA restriction analysis (ARDRA) 16SrRNA gene.Total of 13 ARDRA patterns from digestion of DNA with RsaI restriction enzyme was obtained, indicated higher genetic diversity of X. oryzae pv. oryzae. Phylogenetic analysis revealed a close genetic relationships among isolates. Isolates X. oryzae pv. oryzae 1/96pml and 61pml are closely related with isolates 29d, 59pml, and 60pml although they are isolated from different locations. The other closely related isolates were between X. oryzae pv. oryzae 5mgl with 23d, 38d, 10sbg, 8myd; while 6klt was close to 3ind and 2kr. The result of X. oryzae pv. oryzae genetic diversity can be used as a reference for strain or/isolates selection for development ofbacterial leaf blight resistance in Indonesia.